Pembelajaran Daring Berbasis Youtube dan Open Broadcasting System Bagi Guru-guru MA Muallimin Muallimat Rembang - Oky Dwi Nurhayati; Bayu Surarso; Migunani Migunani; Ahmad Aviv Mahmudi (Buletin Abdi Masyarakat, 2024)
The development of Information and Communication Technology (ICT) as a learning medium requires teachers to have adequate knowledge and skills in integrating it into each subject so that the quality of learning can be improved. One of the phenomena currently visible is that teachers have not been able to use ICT properly as a learning medium. This is caused by many factors, including lack of knowledge and skills, wrong views about ICT. Madrasah Aliyah Mu'allimin Mu'allimat Rembang (M3R) is located on the outskirts of Rembang city, precisely in Kabongan Kidul Village, Rembang District, Rembang Regency. The number of students actively studying is 360 students, taught by 25 teachers and the support of 6 educational staff. . M3R as an institution is also required to provide the latest innovations to form an effective learning process. However, not all teachers and educational staff do not understand the latest innovations that must be used to carry out learning by utilizing internet media which can be utilized optimally. Due to the lack of teachers' ability to create content or learning materials and classroom teaching online, it is necessary to increase the capacity and skills of teachers in creating content and managing online teaching. The method used in the PkM program provides training and practice as well as assistance in the use of information and communication technology in learning activities at schools using open broadcasting systems and YouTube. The outcome of this PkM program is that teachers master and are able to create and use learning media using open broadcasting systems and YouTube and implement them as learning media.Keywords: Information and Communication Technology, open broadcasting system, YouTube, content, learning